Answer: (a) (2w)w 2. (b) 3p. 3 × 4p … y = –5, and z = 3, … x = 7, and x t = 2, t. (d) (kx + 2 kx y. + 2 )y z when k = 3.5, k x = 4, x y = –5, and z = 3,. (e) Step-by-step explanation: hey sorry if its wronge but i tryied 😛 T-T Log in to Reply
Answer:
(a) (2w)w 2. (b) 3p. 3 × 4p … y = –5, and z = 3, … x = 7, and x t = 2, t. (d) (kx + 2 kx y. + 2 )y z when k = 3.5, k x = 4, x y = –5, and z = 3,. (e)
Step-by-step explanation: hey sorry if its wronge but i tryied 😛
T-T
1
[tex]2 \times ( – 7) + 3 = – 11[/tex]